A ANÁLISE DO ERRO SOB A PERSPECTIVA DIDÁTICO-PEDAGÓGICA NO ENSINO-APRENDIZAGEM DA MATEMÁTICA: Um estudo de caso na 5ª série - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2007)
This research investigates the fifth degree students’error in the math learning-teaching context. The research tried to answer th question: “What are the contributions to this process that the work of the teacher, inside the classroom, with the student’s error may bring? The main targets in this work were: to investigate the comprehension that the students have about their own errors and the relationship of it with the learning-teaching process, and, also, to identificate and to describe passages of class and ways of pedagogical treatment given to these errors and strategies of students that may contribute to the development of operation and autonomy in the teaching-learning process by co-operation. The participants of the research were from one only class of fifth degree, from a statual public school, in Parana State, in the school year 2006. This is a qualitative research and a study of case with ethnographic characteristics. In the investigation, we considered the student’s perspective about his own error and the operation observed from the resolution of a test and the discussion about the kind of answers were presented to the questions. This work brings us to the conclusion that: we may give attention to the answers of the students, promotin the Math learning, the operation, the co-operation and the autonomy of thinking; the difficulties found by students in solving the questions derive, the most of times, from the math teaching conditions that do not favor a critical analysis of results, and the exploration of operation strategies for the construction of concepts and mathematical algorithms; the socialization, among the students, of the results from a specific question with the further discussion in different perspectives, with their active participation, about their “own errors” has increased a reflection about the actions of thinking and acception of others opinion.
Keywords: erro; construção do conhecimento; ensino-aprendizagem; matemática; error; knowledge construction; teaching-learning process; mathematics; CNPQ::CIENCIAS HUMANAS::EDUCACAO